AGRONOMIC CHARACTERS OF B. brizantha cv. Xaraés (MG5), UNDER DIFFERENT DOSES OF BIOFERTILIZER OF DAIRY CATTLE - Alonso, R.A.; da Costa, L.V.C. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The production of meat and milk in Brazil is recognized as grazing, and this type of production is one of the great challenges for livestock, due to the implementation of area, adequate use of fertilizers and management to maintain this productivity. Actually the search for sustainability has become part of our daily lives, influencing various daily activities, including agriculture and livestock. Management practices linked to sustainability theory have gained wide space in Brazil and in the world, in this context; more and more rural producers are looking for ways to add value to production by making use of biofertilizers in the production of pasture. Desiring to evaluate the agronomic performance of Brachiaria brizantha cv. Xaraés submitted to different doses of biofertilizer, an experiment was developed at the Institute of Biotechnology - IBIOTEC, belonging to UNIARA, Araraquara - SP, the work was conducted in a greenhouse under completely randomized blocks with five replicates. The treatments consisted of three doses of biofertilizers (5, 10 and 20 m3 / ha-1), and a zero treatment considered the control. The biofertilizer used is from dairy cows, submitted to treatment in anaerobic biodigesters, collected after a convenient period of fermentation. Brachiaria brizantha was evaluated during four consecutive cuts for the evaluation of Green Matter (MV), Dry matter (DM), height (cm), bromatological characters. The application of the dose-independent biofertilizer in relation to the control provided an increase in forage production. It was observed that the treatments with 10 and 20 m3 / ha-1 dose of biofertilizer had better results for plant height (cm), green mass (MV) and dry matter (DM) production, for the bromatology parameter protein content was higher for the treatments that received biofertilizer differing from the control treatment. The results found in this study indicates that it is possible to produce pasture in a sustainable way and without harming the environment, and replacing mineral fertilization.